Controversies in Shoulder Arthroplasty. Issue 4 (December 2015) - Throckmorton, Thomas (Quin); Tashjian, Robert Z.; Keener, Jay D.; Armstrong, April D.; Dines, David M.; Athwal, George S.; Iannotti, Joseph P.; St. Pierre, Patrick; Flanagin, Brody A.; Garofalo, Raffaele; Krishnan, Sumant (Butch); Sajadi, Kaveh R.; et al.
Abstract : Areas of current controversy concerning shoulder arthroplasty include management of glenoid bone loss, the role of patient-specific instrumentation, differing design features of reverse shoulder arthroplasty, and options for humeral fixation in primary and revision procedures. At the 2015 meeting of the American Academy of Orthopaedic Surgeons, shoulder arthroplasty specialists presented a symposium on these controversial topics. In each area, surgeons presented their case for a given position on these issues. This article is a summary of those proceedings.